2003
DOI: 10.1590/s0101-82052003000200001
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of geophysical data as a non-stationary process

Abstract: Abstract. The Kalman-Bucy method is here analized and applied to the solution of a specific filtering problem to increase the signal message/noise ratio. The method is a time domain treatment of a geophysical process classified as stochastic non-stationary. The derivation of the estimator is based on the relationship between the Kalman-Bucy and Wiener approaches for linear systems.In the present work we emphasize the criterion used, the model with apriori information, the algorithm, and the quality as related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
(6 reference statements)
0
2
0
1
Order By: Relevance
“…and the estimated value equation is given by (4) Equation ( 3) is a booton integral and it is usually difficult to solve, but an approach was developed using state variables to describe nonstationary processes (Rocha and Leite, 2003). Kalman and Bucy (1961) have converted the integral in a first-order differential equations system which are more suitable to solve than (3).…”
Section: The Cost Function Of Minimizing Is Given Bymentioning
confidence: 99%
See 1 more Smart Citation
“…and the estimated value equation is given by (4) Equation ( 3) is a booton integral and it is usually difficult to solve, but an approach was developed using state variables to describe nonstationary processes (Rocha and Leite, 2003). Kalman and Bucy (1961) have converted the integral in a first-order differential equations system which are more suitable to solve than (3).…”
Section: The Cost Function Of Minimizing Is Given Bymentioning
confidence: 99%
“…Bannister et al (1999) applied linear and nonlinear filters for fMRI temporal analysis, and their results shown that in general the linear filter is better than the non-linear filter for the signal restoration. In this paper, the Kalman-Bucy filter (Kalman, 1960;Kalman and Bucy, 1961;Rocha and Leite, 2003;Rocha et al, 2007) will be applied to realize the preprocessing of the fMRI data. It is made an adaptation in this method for filtering periodic signals so as to preserve morphology and amplitude of the original signal.…”
Section: Introductionmentioning
confidence: 99%
“…Neste artigo foi aplicado o Filtro de Kalman [4,5,7] para realizar o pré-processamento em dados de FMRI. Esse método é adaptado para filtrar sinais periódicos de modo a preservar a amplitude e a morfologia do sinal original.…”
Section: Introductionunclassified